In vitro versus in vivo protein digestibility techniques for calculating PDCAAS (protein digestibility-corrected amino acid score) applied to chickpea fractions - Tavano, Olga Luisa; Neves, Valdir Augusto [UNESP]; Silva Junior, Sinezio Inacio da (Elsevier B.V., 2016)
Seven different in vitro methods to determine the protein digestibility for chickpea proteins were considered and also the application of these methodologies for calculating PDCAAS (protein digestibility-corrected amino acid score), seeking their correlations with the in vivo methodology. In vitro digestibility of raw and heated samples were determined using pepsin-pancreatin hydrolysis, considering soluble nitrogen via Kjeldahl (ppKJ) and hydrolysed peptide linkages using trinitrobenzenesulfonic acid and o-phthaldialdehyde. In vitro digestibility was also determined using trypsin, chymotrypsin and peptidase (3-Enz) or trypsin, chymotrypsin, peptidase and pronase solution (4-Enz). None of the correlations between in vitro and in vivo digestibilities were significant (at p < 0.0500), but, strong correlations were observed between PDCAAS calculated by in vitro and in vivo results. PDCAAS-ppKJ, PDCAAS-3-Enz and PDCAAS-4-Enz presented the highest correlations with in vivo method, r = 0.9316, 0.9442 and 0.9649 (p < 0.0500), respectively. The use of in vitro methods for calculating PDCAAS may be promising and deserves more discussions. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Protein digestibility; In vitro digestibility; PDCAAS; Chickpea; Protein fractions